An improved measurement of the Ca2+-binding affinity of fluorescent Ca2+ indicators. (May 2018) - Tran, Van; Park, Michael C.H.; Stricker, Christian
Graphical abstract: Highlights: Fluorescent Ca 2+ indicators are calibrated in physiologically relevant solutions. Measurement of the free Ca 2+ concentration in calibrating solutions is critical. Calculation of [Ca 2+ ] with Maxchelator underestimates the Ca 2+ -binding affinities. This causes underestimates of Ca 2+ rises but overestimates of Ca 2+ binding ratios. Abstract: Fluorescent Ca 2+ indicators are widely used to measure the intracellular Ca 2+ concentration ([Ca 2+ ]i ) in living cells, including neurons. By calibrating an indicator in solutions that mimic the main ionic constituents of the actual cytoplasm, [Ca 2+ ]i can be determined from the measured fluorescence intensity. However, different studies have reported considerably different Ca 2+ -binding affinities ( K d ) for the same indicator, even though they used calibrating solutions with similar compositions. In this paper, we present a method to accurately determine the K d values of non-ratiometric Ca 2+ indicators in solutions that mimicked a standard patch-clamp internal solution. The free Ca 2+ concentration ([Ca 2+ ]) in these solutions, which was set by either EGTA or HEDTA, was measured with a Ca 2+ -selective macroelectrode. We found that such a measurement was critical for an accurate calibration of the Ca 2+ indicators. The K d values of OGB-1, OGB-6F, fluo-5F, and fluo-4FF were 0.26 ± 0.01, 8.7 ± 0.4, 1.00 ± 0.05, and 23.0 ± 0.7 μM, respectively. Calculating [Ca 2+ ] with Maxchelator, a widely used computer program, led to a significant underestimation of the K d values of OGB-6F, fluo-5F, and fluo-4FF. This is because the purity of EGTA was considerably less than that advertised by the manufacturer. In addition, the K d value of HEDTA was overestimated by Maxchelator. Therefore, besides batch-to-batch variations, the fact that [Ca 2+ ] in the calibrating solutions of many studies was estimated with Maxchelator is very likely a reason for the different published values of K d of Ca 2+ indicators. Using a reaction-diffusion model to reproduce Ca 2+ rises in a nerve terminal, we further showed that incorrect calibration of fluorescent Ca 2+ indicators can underlie the large variation of the endogenous Ca 2+ binding ratio between different types of excitatory synapses.